Development of an RGB color analysis method for controlling uniformity in a long-length GdBCO coated conductor. (16th November 2015) - Kim, Tae-Jin; Lee, Jae-Hun; Lee, Yu-Ri; Moon, Seung-Hyun
Abstract: Reactive co-evaporation-deposition and reaction (RCE-DR) is a very productive GdBa2 Cu3 O7− x (GdBCO) coated conductor (CC) fabrication process, which involves the fast phase conversion of an amorphous film formed by co-evaporation of three metal sources, Gd, Ba and Cu, and thus reduces the time and cost for fabrication of a GdBCO CC. We routinely use quartz crystal microbalance (QCM) to measure and control the evaporation rates of each metal source to keep a constant nominal composition of the superconducting (SC) layer. However, in the case of kilometre long GdBCO CC fabrication, evaporation rates measured by QCM do not exactly reflect deposition rates onto the substrate as source levels decrease, and thus an RGB color analysis method for quality control is designed. With this RGB color analysis method, it is possible to measure the composition of the converted SC layer very close to the actual composition, even in real time. We set up the RGB color analysis program by establishing a database, where RGB color values are matched to composition of the SC layer, and as a result of applying the program to the RCE-DR process, could fabricate high quality GdBCO CC with average critical current of 561 A cm −1 and 95% uniformity along a 1 km length.